Realising carbide ultrafast homogenisation under pulsed electric current. Issue 11 (24th July 2022) - Hao, Jianqiao; Qin, Shuyang; Yan, Longge; Zhang, Xinfang
Abstract : Network carbides, as a deleterious precipitate to the mechanical properties of bearing steel, are difficult to eliminate by traditional heat treatment. Here, an innovative strategy to rapidly dissolve network carbides using electric current pulses to improve the uniformity of the microstructure is proposed. The results show that the diffusion driven by electromigration is significantly enhanced compared to traditional heat treatment due to the high-density current on the network carbide surface. Furthermore, grain boundaries as fast diffusion paths play a key role in accelerating the dissolution of network carbides.